We Are Not Dreamers : Undocumented Scholars Theorize Undocumented Life in the United States - Negrón-Gonzales, Genevieve; Abrego, Leisy J. (Book collections on Project MUSE., 2020)
"WE ARE NOT DREAMERS is a collection of ten auto-ethnographic essays by undocumented, DACAmented, and formerly undocumented scholars in California who relay their experiences of illegality, as well as insights into their broader research on migration. Co-editors Leisy Abrego and Genevieve Negrón-Gonzales intentionally center these voices to intervene within a field that theorizes the experiences of undocumented people without truly giving the undocumented people a space to be knowledge-producers themselves. These scholars face particular challenges-- personally, politically, and in their research -- and are uniquely positioned to provide nuanced insights on illegality, citizenship, education, and belonging that have the potential to grow the field of undocumented studies, shift understandings, and remake the bodies of literature which speak to their experiences. Moreover, their scholarship resists the harmful "Dreamer" narrative perpetuated by non-profits, DC lobbying groups, journalists, researchers, and the government, ultimately challenging notions of the American Dream and the "good immigrant" narrative to push for more inclusive practices within the academy and more comprehensive immigration policies on the national stage. The first half of the book explores the connection between identity, illegality, and resistance as a way to critically analyze how undocumented migrants have been "made" through these processes. In chapter 2, Grecia Mondragón highlights the pressures and expectations that students are forced to navigate within higher education while carrying the weight of the Dreamer narrative. In chapter 5, Gabriela Garcia Cruz focuses on the political engagement of older undocumented women activists and how this activism reshapes lived experiences of citizenship and dignity. The second half of the book centers quotidian life to imagine what an intersectional analysis of undocumented status looks like by grappling with the structures of relationships, family, and identity. Audrey Silvestre, in chapter 8, centers the everyday experiences of undocumented trans women and the ways in which they have reclaimed spaces of joy amidst violent hate crimes. Chapter 9 by Lucy León emphasizes the insidious effects of immigration policy that determine how people must represent their love to one another and to the state. The book significantly contributes to how we understand the ways undocumented actors move through the spaces of daily life and in doing so, remake those spaces. This book will be of interest to students and scholars in Latinx and Chicanx studies, sociology, anthropology, studies of social movements, and studies of the experiences of undocumented people in the United States"--